2020
DOI: 10.51278/bce.v1i1.87
|View full text |Cite
|
Sign up to set email alerts
|

The Problems and Solutions for Learning Activities during Covid-19 Pandemic Disruption in Hidayatul Insan Pondok School

Abstract: This study aimed to determine students' obstacles when learning online systems from home during the Covid-19 pandemic. This type of research is qualitative, and the method used in collecting information is in the form of online questionnaires to class X students at MA Hidayatul Insan Palangka Raya as long as the students carry out community service, namely the Community Service Program (KKN) in institutions that collaborate with supervisors in writing this journal article. The findings of this study indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…As a result, these findings are the expected for short measures for detection (Domínguez-Lara & Merino-Soto, 2018) and they are enough for using the scale in online research contexts, as well as contributing to detection, diagnostic, and intervention inside the educational field (Netemeyer et al, 2003). This information is more useful nowadays because as it has been experienced during the last year, the coronavirus disease (COVID-19) pandemic has provoked several changes in our daily routine and the substitution of the paper questionnaires by online questionnaires is an important finding that must be kept for our present and future society (Raminah et al, 2021), Finally, it is necessary to highlight that the current piece of research is the first to examine sex invariance of the online version of DASS-21 in Ecuadorian undergraduates (third objective). The This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, these findings are the expected for short measures for detection (Domínguez-Lara & Merino-Soto, 2018) and they are enough for using the scale in online research contexts, as well as contributing to detection, diagnostic, and intervention inside the educational field (Netemeyer et al, 2003). This information is more useful nowadays because as it has been experienced during the last year, the coronavirus disease (COVID-19) pandemic has provoked several changes in our daily routine and the substitution of the paper questionnaires by online questionnaires is an important finding that must be kept for our present and future society (Raminah et al, 2021), Finally, it is necessary to highlight that the current piece of research is the first to examine sex invariance of the online version of DASS-21 in Ecuadorian undergraduates (third objective). The This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Discussionmentioning
confidence: 99%
“…The research results by Habibi et al (2021) show that in dealing with Covid-19, Islamic education units face three serious obstacles: technological, financial, and pedagogical barriers. In contrast, Rahimah et al (2020) found that students in Islamic education units experienced obstacles during teaching and learning activities due to the online learning system during the Covid-19 pandemic. They are students' difficulty understanding teaching materials, lack of facilities or learning media, insufficient internet quota when studying from home, and lack of parents' technology media literacy.…”
Section: Introductionmentioning
confidence: 90%
“…Di Indonesia sendiri pemerintah yang dibantu pihak-pihak terkait melakukan berbagai macam langkah cepat demi meminimalisir dan memutus penularan virus covid-19 ini. Dari mulai diterapkannya physical distancing, Work from home (belajar dari rumah), hingga saat ini sudah banyak kepala daerah yang mengajukan dan menjalankan PSBB (Pembatsan Sosial Berskala Besar) di daerahnya demi menekan angka pertumbuhan dari virus covid-19 ini (Said, & Muslimah, 2021;Rahimah, et al, 2020;Mahmudah, et al, 2021). Banyak kegiatan umum maupun lembaga-lembaga yang harus ditutup atau tidak boleh dilakukan untuk sementara waktu.…”
Section: Pendahuluanunclassified